Single Mo Atom Supported on Defective Boron Nitride Monolayer as an Efficient Electrocatalyst for Nitrogen Fixation: A Computational Study - Zhao, Jingxiang; Chen, Zhongfang (Journal of the American Chemical Society, 2017)
The production of ammonia (NH3) from molecular dinitrogen (N2) under mild conditions is one of the most attractive and challenging processes in chemistry. Here by means of density functional theory (DFT) computations, we systematically investigated the potential of single transition metal atoms (Sc to Zn, Mo, Ru, Rh, Pd, and Ag) supported on the experimentally available defective boron nitride (TM–BN) monolayer with a boron monovacancy as a N2 fixation electrocatalyst. Our computations revealed that the single Mo atom supported by a defective BN nanosheet exhibits the highest catalytic activity for N2 fixation at room temperature through an enzymatic mechanism with a quite low overpotential of 0.19 V. The high spin-polarization, selective stabilization of N2H* species, or destabilizing NH2* species are responsible for the high activity of the Mo-embedded BN nanosheet for N2 fixation. This finding opens a new avenue of NH3 production by single-atom electrocatalysts under ambient conditions.